PERANCANGAN PENILAIAN KINERJA PEGAWAI BERDASARKAN KOMPETENSI SPENCER - Setiyanti, Sri Wiranti; Sujadi, Sujadi (JURNAL STIE SEMARANG, 2012)
Employee performance evaluation using the competency Spencer will feel the benefits to the agencies that implement incentives other than salary. Providing incentives for bias are briefly defined themselves as 'extra pay for extra performance'. Thus the income that will be given to employees who excel will be formulated as follows: Income = salary + incentives . Employee incentive system design is determined using the method of division of profit, which is an incentive plan that combines many or all employees in a joint effort to achieve multiple objectives such as productivity of the company. To apply there are 7 (seven) steps that must be considered, namely: First targeting the general plan. Secondly, the establishment of specific performance measures. Third, determination of sources of funding incentives. Fourth, establishing a method to divide and distribute the gains of employees. The method used for calculating employee incentives are as follows: (a) the percentage increase in the value of work performance standards set forth as follows: [(employees working Achievement - Achievement standard employment) / Achievement standard employment) x 100%]. (B) Provision of incentives based on a percentage increase. Incentives will be awarded based on the percentage increase in the value of performance achieved by the employee. Percentage increase in the value of work performance standards set are shown by an employee will be compared with the total percentage increase in value throughout the employee work performance. So it will get a final value, which is the final value will be multiplied by the funds allocated for th e incentive, to find out who obtained an employee incentive. Example: Funds provided for incentives in the month of X is 10 million. With a value of 2.5 standard work performance and the total percentage increase in the value of employee work performance throughout 1000%, then the incentives received by an employee who has a Y value of 2.709 job performance are: (a)% increase in value of employee work performance Y: [(2.709 - 2.5) / 2.5)] x100% = 8.36%, and (b) Incentives received by employee Y: (8.36% / 1000%) x Rp. 10.000.000, - = Rp. 83600.00. Fifth, the determination of payment used. Sixth, determining how often the bonus is paid. Seventh, the development of employee involvement systems. Research on the relationship of performance appraisal with the provision of incentives have been made by Eko Nurmianto, Nurhadi Siswanto and Sanusi sweep. In his study entitled designing competency-based employee performance appraisal Spencer Method with Analytical Hierarchy Process (Case Studies in Sub Department of Irrigation, Public Works Department, City of Probolinggo) that is generated by profit-sharing incentive system, based on Employee Performance Value will reflect incentives real incentives so that inaccuracies can be reduced. Then  the  work performance assessment should  use  the  assessment criteria that  reflect the working conditions and given appropriate weight to be able to motivate employee productivity